Strategi Direct Fundraising dengan Koin LAZISNU Padangsidimpuan - Risna Hairani Sitompul; Siti Berlian Harahap (Journal of Islamic Social Finance Management, 2021)
ABSTRACT Fundraising strategy is a strategy carried out by an institution to raise funds such as the strategy carried out by LAZISNU Padangsidimpuan City in increasing ZIS fund receipts, which is useful for knowing the implementation of fundraising at LAZISNU. This study uses a qualitative approach with the type of field research. Sources of data in the form of primary data and secondary data. Collecting data with the method of observation, interviews and documentation. The data analysis technique used descriptive analysis method. The data validity technique was using triangulation, namely source triangulation and method triangulation. The results showed that LAZISNU Padangsidimpuan City implemented several strategies to raise funds. The fundraising strategy implemented by LAZISNU Padangsidimpuan City uses 2 methods, namely Direct Fundraising and Indirect Fundraising. Direct Fundraising consists of several programs, namely Zakat Pickup Service, Personal ZIS, Direct Mail, Nusantara Coin Movement and LAZISNU Glass Box, while the Indirect Fundraising method is carried out with the Socialization program. Keywords : Fundraising, Zakat, LAZISNU  ABSTRAK Strategi Fundraising merupakan strategi yang dilakukan oleh sebuah lembaga untuk menghimpun dana seperti strategi yang dilakukan oleh LAZISNU Kota Padangsidimpuan dalam meningkatkan penerimaan dana ZIS, yang berguna untuk mengetahui implementasi fundraising pada LAZISNU. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian lapangan (field research). Sumber data berupa data primer dan data sukunder. Pengumpulan data dengan metode observasi, wawancara dan dokumentasi. Teknik analisis data menggunakan metode analisis deskriptif. Teknik keabsahan data dengan menggunakan triangulasi yaitu triangulasi sumber dan triangulasi metode. Hasil penelitian diketahui bahwa LAZISNU Kota Padangsidimpuan menerapkan beberapa strategi guna menghimpun dana. Strategi fundraising yang diterapkan oleh LAZISNU Kota Padangsidimpuan menggunakan 2 metode yaitu Direct Fundraising dan Indirect Fundraising. Direct Fundraising terdiri atas beberapa program yaitu Layanan Jemput Zakat, Personal ZIS, Direct Mail, Gerakan Koin Nusantara dan Kotak Kaca LAZISNU, sedangkan untuk metode Indirect Fundraising dilakukan dengan program Sosialisasi. Kata Kunci : Fundraising, Zakat, LAZISNU